PENGARUH KEMUDAHAN TRANSAKSI DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE DI KALANGAN MAHASISWA JURUSAN MANAJEMEN FEB UHO - Dzulfikri Azis Muthalib (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2026)
This study aims to examine the effect of transaction ease and trust on purchase decisions on marketplace platforms among Management students of the Faculty of Economics and Business, Halu Oleo University (FEB UHO). A quantitative approach with an explanatory survey design was employed. Data were collected from 100 active Management students who had made at least one purchase through a marketplace application within the last three months, selected through purposive sampling. Data were gathered using a structured questionnaire and analyzed through multiple linear regression with the assistance of SPSS software. The results show that transaction ease and trust each have a positive and significant effect on purchase decisions. Simultaneously, both variables significantly influence purchase decisions and account for a substantial proportion of its variance. These findings suggest that marketplace providers need to continuously enhance application usability and strengthen consumer trust in order to encourage purchase decisions among young, digitally literate consumers such as university students.